4(-7+2m)+4(1-m)=-36

Simple and best practice solution for 4(-7+2m)+4(1-m)=-36 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(-7+2m)+4(1-m)=-36 equation:


Simplifying
4(-7 + 2m) + 4(1 + -1m) = -36
(-7 * 4 + 2m * 4) + 4(1 + -1m) = -36
(-28 + 8m) + 4(1 + -1m) = -36
-28 + 8m + (1 * 4 + -1m * 4) = -36
-28 + 8m + (4 + -4m) = -36

Reorder the terms:
-28 + 4 + 8m + -4m = -36

Combine like terms: -28 + 4 = -24
-24 + 8m + -4m = -36

Combine like terms: 8m + -4m = 4m
-24 + 4m = -36

Solving
-24 + 4m = -36

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '24' to each side of the equation.
-24 + 24 + 4m = -36 + 24

Combine like terms: -24 + 24 = 0
0 + 4m = -36 + 24
4m = -36 + 24

Combine like terms: -36 + 24 = -12
4m = -12

Divide each side by '4'.
m = -3

Simplifying
m = -3

See similar equations:

| (80-x)+(90-2x)=180 | | x^2-x=23 | | 79=-5(2x+3)-7(-4+8x) | | 12x+13=56 | | 12+x(13)=12 | | 6(3x-8)=14x-20 | | 3z^2-13z+4=0 | | z^2-10z+9=0 | | -29=592a-1+2a | | 2x+1x+1x=500000 | | 5x+40+2x=180 | | -9n(7n-6)=0 | | 2x+1x+1x=900000 | | 6x=-6x-3(5-3x) | | (4x-12)(7x+6)=0 | | (4x-12)(7x+6)=0 | | 3x+1x+1x=900000 | | 27x^2+12=36x | | 67=N-84 | | N+6=15 | | 3(d+2e)-11d= | | k-(-8k)= | | 3*(2x-4)=24 | | 48-3x=15x+22 | | 2d-5-3d-8= | | -3p+5p= | | -32-3w-5w=0 | | 8t+t= | | 2*(2x-4)=24 | | 6x+2y=22 | | 2*(2x+3)=3*(x+10) | | 8a+2=6-10a |

Equations solver categories